2017
DOI: 10.1177/0306624x17734798
|View full text |Cite
|
Sign up to set email alerts
|

Problem Analysis in Community Violence Assessment: Revealing Early Childhood Trauma as a Driver of Youth and Gang Violence

Abstract: Problem analysis conducted by a university-based research partner can provide communities with data-driven options to address the local drivers of serious youth and gang violence. Situated in Worcester, Massachusetts, this article describes how subsequent to early childhood trauma being identified as a potential driver of adolescent and young adult violence; problem analysis using local data confirmed that being the victim or witness of a traumatic incident before the age of 12 years was significantly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Clinical and epidemiological studies have shown that individuals who have experienced childhood maltreatment/ trauma have an increased risk for violent behavior later in life (7,8). Childhood maltreatment is also associated with an increased risk of developing psychosis (9-11) compared to the general population, and most probably with an increased risk of violent behavior among patients with psychosis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and epidemiological studies have shown that individuals who have experienced childhood maltreatment/ trauma have an increased risk for violent behavior later in life (7,8). Childhood maltreatment is also associated with an increased risk of developing psychosis (9-11) compared to the general population, and most probably with an increased risk of violent behavior among patients with psychosis (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Our results also demonstrated significant associations between polytraumatization and delinquency and drug distribution. Previous research among gang members has only identified the association between trauma and perpetration of violence, rather than including other delinquent acts (Ross & Arsenault, ). Although directionality was not specified in our study, it has been suggested that the relation between trauma and delinquency among adolescent gang members may be reciprocal, as one study demonstrated that trauma exposure increased the risk for delinquency, and gang membership increased the risk for additional traumatization (Begle et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…There are also links between traumatization and the perpetration of violence (Hartinger‐Saunders et al., ; Maschi, ; Ross & Arsenault, ; Shaffer & Ruback, ), drug use (Lin, Cochran, & Mieczkowski, ; Loeber et al., ), and drug distribution among adolescents. Previous studies have demonstrated that gang members are more likely to engage in delinquent behaviors (De La Rue & Espelage, ; Harper et al., ) and drug distribution (Bjerregaard, ) than non–gang members.…”
mentioning
confidence: 99%
“…Illicit substance use has also been considered both a negative outcome associated with trauma and a risk factor for later problems (Carliner et al, 2016). A peer group that engages in illicit drug use and other crime can be a related risk factor that increases the likelihood of negative outcomes, especially for individuals with a history of trauma (Ross & Arsenault, 2018). While many unique risk factors, such as peer group, are difficult for clinicians to remove, research suggests that increasing the presence of protective factors can counter the effects of these risk factors (Abrahams, 2009).…”
Section: Protective Factorsmentioning
confidence: 99%